1974
DOI: 10.1080/00362177485380481
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure ofCandida albicansafterin vitrotreatment with miconazole

Abstract: Electron microscopic examination on Candida albicans yeast cells after exposure in vitro to different doses ofmiconazole revealed that it exerts its effect primarily on the plasmalemma and the cell wall. After exposing cultures to drug concentrations of 10-nM and 10-sM progressive degradation of plasmalemma and cytoplasmic organelles were seen. Injured parts of cellular material were sequestered from the rest of the cytoplasm and extruded into the central vacuole. A similar degradation occurred at the cell per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…The ultrastructural damage caused by azoles is well documented [8][9][10][11] and has been reviewed by MUller [12]. The ultrastructural oxiconazole-related changes observed in the present study are qualitatively the same as found with amorolfine.…”
Section: Resultssupporting
confidence: 81%
“…The ultrastructural damage caused by azoles is well documented [8][9][10][11] and has been reviewed by MUller [12]. The ultrastructural oxiconazole-related changes observed in the present study are qualitatively the same as found with amorolfine.…”
Section: Resultssupporting
confidence: 81%
“…Yet, alteration of cell wall structure has been detected with scanning and transmission electron microscopy (68,69).…”
Section: Morphology Ultrastructure and Permeabilitymentioning
confidence: 99%
“…Econazole, fenticonazole, isoconazole and miconazole all caused convolutions and wrinkles in the cell wall [6]. The folds in the cell walls of miconazole-treated cells may correspond to focal areas where membranous material had been deposited between the cell wall and the plasmalemma [8,10]. Another feature of the action of miconazole is that chains of inter-connected cells were observed with pronounced necks [9] and this was also observed with cholic acid-treated cells (Fig.…”
Section: Discussionmentioning
confidence: 63%